Chronic cough in the Holmes-Adie syndrome: association in five cases with autonomic dysfunction. Issue 4 (1st October 1998) - Kimber, J; Mitchell, D; Mathias, C J
Abstract : The Holmes-Adie syndrome consists of unilateral or bilateral tonic pupils with near light dissociation and tendon areflexia. It is associated with autonomic disturbances affecting sudomotor and vasomotor function. Five such patients are reported on who also had a troublesome chronic dry cough, which was of unknown aetiology and was resistant to a range of treatments. The cough may be related to involvement of afferent or efferent pathways in the vagus. Chronic cough may be an accompaniment in the Holmes-Adie syndrome, like other forms of autonomic dysfunction.